How Does Disease Severity Affect Clinical Outcomes and Economic Burden of Patients with COPD —— A Retrospective Population-Based Cohort Study in Tianjin, China - Wang L; Huang K; He X; Zhang J; Yang T; Wu J (International Journal of COPD)
Lei Wang,1,2,* Ke Huang,3– 5,* Xiaoning He,1,2 Jiahui Zhang,1,2 Ting Yang,3– 5 Jing Wu1,2 1School of Pharmaceutical Science and Technology, Tianjin University, Tianjin, People’s Republic of China; 2Center for Social Science Survey and Data, Tianjin University, Tianjin, People’s Republic of China; 3Department of Pulmonary and Critical Care Medicine, China-Japan Friendship Hospital, Beijing, People’s Republic of China; 4National Clinical Research Center for Respiratory Diseases, Beijing, People’s Republic of China; 5Institute of Respiratory Medicine, Chinese Academy of Medical Science, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Wu, School of Pharmaceutical Science and Technology, Tianjin University, No. 92 Weijin Road, Nankai District, Tianjin, 300072, People’s Republic of China, Email jingwu@tju.edu.cn Ting Yang, Department of Pulmonary and Critical Care Medicine-Japan Friendship Hospital, No. 2, East Yinghua Road, Chaoyang District, Beijing, 100029, People’s Republic of China, Email zryyyangting@163.comIntroduction: Quantifying the disease burden across severity levels is essential for early intervention and effective management of chronic obstructive pulmonary disease (COPD). This study aimed to clarify the effect of severity on disease burden by comparing clinical and economic outcomes stratified by disease severity based on the Global Initiative for Chronic Obstructive Lung Disease (GOLD) in a Chinese setting.Methods: A retrospective population-based cohort study was conducted using electronic health records of 80 hospitals (2016– 2019). Patients (≥ 40 years) diagnosed with COPD (ICD-10: J44) between 2017 and 2018 were identified and further classified into high (GOLD E) or low (GOLD A/B) exacerbation risk groups based on 12-months pre-index exacerbation history. GOLD groups A, B, and E were categorized based on exacerbation history and prior symptom burden. Clinical and economic outcomes were examined during 12-months follow-up, including incidence and time intervals between exacerbations, mortality, healthcare resource utilization, and direct medical costs.Results: Among 6759 COPD patients (mean age 68.36 ± 11.46 years, 62.4% male), patients in group E (N=2378) showed significantly worse outcomes than group A/B (N=4381): 57% higher exacerbations risk (90.5 vs 70.5%, adjusted hazard ratio [HR]=1.57; 95% CI: 1.48– 1.67), 31% higher risk of all-cause mortality (11.6 vs 6.6%, HR=1.31; 95% CI: 1.10– 1.57), and 1.7-fold higher COPD-related total costs (Chinese yuan [CNY] 21,156 vs 12,457, adjusted difference CNY 4238) during follow-up. Notably, the incidence rates of overall exacerbation, total costs increased progressively from group A to B to E in the year following the index date.Conclusion: Poor prognosis and high economic burden were observed among Chinese patients with COPD. Higher disease severity was associated with increased risk of exacerbation, all-cause mortality, and economic burden. These findings underscore the need for early intervention in patients with mild COPD to prevent disease progression, subsequent exacerbations, and rising economic impacts.Keywords: chronic obstructive pulmonary disease, acute exacerbation, healthcare resource utilization, costs, disease severity